Optimalisasi Pengisian Edukasi Keperawatan pada ERM dengan membuat Komitmen Bersama antara Kepala Unit dan Perawat Pelaksana dengan menggunakan Pendekatan Metode PDSA: Optimizing Nursing Education Content in ERM by making a Joint Commitment between the Head of the Unit and the Implementing Nurse using the PDSA Method Approach - Limara Sartika Marunduh, Dian; Dian Ellina, Agusta (Chakra Brahmanda Lentera Institute, 2024)
The Plan-Do-Study-Act (PDSA) method is an approach to test the changes implemented to ensure continuous quality improvement. The four steps in the PDSA help guide the thinking process by breaking down the task into technical steps, then evaluating the results, improving them, and retesting them. The project to optimize the filling of ERM in the nurse education section requires the commitment of all nurses and the head of the Inpatient I room at Bali Royal Hospital. The concept in the search for the root of the problem uses a fishbone diagram, a scoring method to arrange the priority of issues that must be solved. The case study was carried out in Inpatient Room I of Bali Royal Denpasar Hospital with a total of 29 nurses and 1 room head. The implementation of optimizing the filling of nursing education at ERM began with a focused group discussion that resulted in an agreement/commitment between the nurse and the head of the room with his supervision function, then the implementation was evaluated using the P-D-S-A method at Bali Royal Hospital. The analysis of the implementation results obtained quite good results, with an achievement of 42% in the first week and increased to 51% in the second week. The application of the joint commitment model between the implementing nurse and the supervision of the head of the room through the P-D-S-A method approach in optimizing the filling of nursing education in ERM which is a form of effort to improve the quality in nursing is important to be carried out on an ongoing basis. The PDSA cycle that is carried out consistently and carried out in conjunction with the commitment of the nurse and the role of supervision from the head of the room will produce better results.